Influence of Carboxypeptidases on Cocoa Specific Aroma Precursors and Methylpyrazines in Under-Fermented Cocoa Beans - Ikrawan, Yusep (2003)
A study on the influence of two carboxypeptidases on cocoa specific aroma precursors and methylpyrazines in under..fermented cocoa beans was carried out. Cocoa beans, which were fermented for three days using wooden box were used as samples. The beans were powdered and then incubated at 45°C for 6, 12, 24 and 48 h. Protein content, carboxypeptidase activity, cocoa storage protein, free amino acids, peptide profiles and methylpyrazines concentration were determined. Commercial carboxypeptidase B from porcine and carboxypeptidase Y from baker's yeast were used separately for digestion of cocoa storage protein. Protein content decreased during 3 days of fermentation. Three major bands of cocoa storage protein were found using SDS-P AGE. Carboxypeptidase activity increased after one day, but later decreased between two and three days of fermentation. During three days of fermentation, free amino acids increased and about 50 to 62% of hydrophobic free amino acids were produced. Hydrophobic peptides in unfermented cocoa beans were considerably higher as compared to underfermented beans. However, their peptide profiles were very similar for all samples taken at one to three days of fermentation. The concentration of 2,5- dimethyl-, 2,3,5-trimethyl- and 2,3,5,6-tetramethylpyrazines were low after one day and increased during two to three days of fermentation. The degradation of cocoa storage protein from the samples treated with 5 % and 10% of carboxypeptidase B and carboxypeptidase Y revealed similar peptide bands with those of the untreated samples. Hydrophobic free amino acids (alanine, valine, isoleucine, leucine,phenylalanine and tyrosine) were predominantly produced in the samples treated with 5% and 10% of carboxypeptidase B and Y. The pep tides profile were very similar with those of the control (well fermented beans). Digestion with carboxypeptidase B and carboxypeptidase Y did not have a significant effect on the concentration of 2,5-dimethyl-, 2,3,5-trimethyl- and 2,3,5,6-tetramethylpyrazines. Concentrations of acidic amino acid (aspartic, glutamic), hydrophobic amino acids (leucine, alanine, phenylalanine, tyrosine, valine and isoleucine), others (proline, methionine, cysteine, tryptophane, lysine, serine, glysine, histidine,arginine and threonine) and total of amino acids in the untreated adn treated samples with 5% and 10% of carboxypeptidase B and carboxypeptidase Y were significant decreased by roasting at 150°C for 15 min. The proportions of peptides also decreased upon roasting. Peptide profiles revealed very similar chromatogram with those of untreated sample. The concentration of 2,3,5,6-tetramethylpyrazine was significantly higher for samples treated with carboxypeptidase B compared to 2,5-dimethyl- and 2,3,5-trimethylpyrazine. However, the concentration of 2,3,S-trimethylpyrazine was the highest (1727.86 µg 100g-1) in the sample with carboxypeptidase B that had been incubated for 24 h. Cocoa liquor made from under-fermented cocoa beans treated with carboxypeptidase B and carboxypeptidase Y were more bitter, astringent, acidic, higher in off-flavour and possessed weaker cocoa flavour compared to the reference (Ghanaian cocoa) sample. There were no significant differences (p>0.05) among samples treated with 5% and 10% of carboxypeptidases B and Y; however, there was significant correlation (P<0.05) between methylpyrazines and cocoa flavour attribute and also with hydrophobic free amino acids in the samples treated with both enzymes. The overall findings indicate that carboxypeptidase B from porcine pancreas was efficient for the formation of cocoa specific aroma precursors.